MENGEMBANGKAN KEMAMPUAN KETERAMPILAN MINAT MEMBACA PA-DA PESRTA DIDIK DI SEKOLAH DASAR MELALUI GAMBAR ANIMASI SE-BAGAI MEDIA PEMBELAJARAN - Tanti Aplianti; Nana Hendra Cipta; Siti Rokmanah (STKIP Subang, 2023)
Animited cartoon film media is one of the media that can be used in the learning process to improve reading skills in elementary schools. The learning media can increase students’ anthusiasm for learning so that student can stimulus material quickly. Through animated videos it is hoped that it can help studeents in the learning process. Based on the data found the animated media is very effective in learning, especially in reading skills in elementary schools, so that students do not experience difficulties in the learning process.